2005
DOI: 10.1111/j.1365-2303.2004.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and accuracy of intraoperative imprint cytology of sentinel lymph nodes in breast cancer

Abstract: Imprint of SLN biopsy can identify a negative axilla with high accuracy (specificity 99.2%). Overall sensitivity is only 36.5%, but macrometastases are detected in 77% which is important for performing ALDN in one session with operation of primary tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Another specific disadvantage of FS is that in case of a small-sized SLN the possibility of tissue destruction with parallel absence of material for final histological examination is apparent. Therefore, FS cannot be performed on occasion because of inadequate safety of protecting the permanent specimen 3033. Moreover, LC cells are morphologically similar to lymphoid cells, thus making identification of metastases more challenging on both IC and definitive postoperative histology 34.…”
Section: Discussionmentioning
confidence: 99%
“…Another specific disadvantage of FS is that in case of a small-sized SLN the possibility of tissue destruction with parallel absence of material for final histological examination is apparent. Therefore, FS cannot be performed on occasion because of inadequate safety of protecting the permanent specimen 3033. Moreover, LC cells are morphologically similar to lymphoid cells, thus making identification of metastases more challenging on both IC and definitive postoperative histology 34.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,11,15,16 The reasons for low sensitivity in certain studies may be poor quality of the imprints, presence of metastatic cells under the capsule of the lymph node or sometimes the larger group of cells is not imprinted because the cohesion between the epithelial cells is more than between the lymphoid cells. 15 The other limitations of practical significance are low volume metastases, metastases from lobular or low grade ductal carcinomas or a diffuse unicellular infiltrating pattern may remain undetected. 17 A few studies have reported sensitivity of imprint smears even better than frozen section which may be because of less number of cases having micrometastases and only a small percentage of lobular carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] The techniques used for the intraoperative evaluation of SLNs include frozen section analysis and imprint cytology. [20][21][22][23][24][25][26][27] Frozen section analysis has the advantage of high sensitivity but the disadvantages that the sections may undergo artefactual changes, tissue is consumed, and the procedure is time consuming. In contrast, imprint cytology can provide clear cytological details and a rapid diagnosis, preserving the tissue for permanent sections.…”
Section: Introductionmentioning
confidence: 99%